Proportions and risk factors of chronic obstructive pulmonary disease and preserved ratio impaired spirometry, and association with small airway disease, in the positive screening older population from China: a cross-sectional study - Le Sang; Xia Gong; Yunlei Huang; Jian Sun (BMC Pulmonary Medicine, 2024)
Abstract Background Early diagnosing Chronic Obstructive Pulmonary Disease (COPD) is relatively difficult. Therefore, the concepts of preserved ratio impaired spirometry (PRISm) and small airway disease (SAD) were proposed to achieve early diagnosis for COPD. Besides, the occurrence of COPD is positively related to age. However, the relationship among COPD, PRISm, and SAD still requires clarification. Thus, we estimated the proportions and risk factors of COPD and PRISm in the positive screening participants, and searched the methods of early diagnosing COPD via the SAD indicators. Methods A total of 53,641 residents aged more than 60 years old from Shaoxing City, Zhejiang Province, China, completed a series of screening projects. And 2327 of positive screening participants ultimately finished bronchodilator tests. The data were statistically analyzed to figure out the proportions and risk factors of COPD and PRISm, and the efficacy of early diagnosing COPD by the SAD indicators. Results Totally 2229 positive screening participants were included, the proportion of PRISm was 6.3% (141/2229), and of COPD was 78.2% (1743/2229). Statistical analyses showed that COPD patients were more likely to be smokers, males, and older. And COPD patients had higher questionnaire scores, meaning that they were more prone to have family history of respiratory diseases and more severe respiratory symptoms. Additionally, COPD patients had lower maximal mid-expiratory flow (MMEF) pred, forced expiratory flow (FEF) 75pred, and FEF50pred. And we found that male sex and presence of respiratory symptoms might lead to COPD and PRISm. Also, the methods of early diagnosing COPD through the SAD indicators might be acceptable. Conclusion There is a close association between COPD and decreased small airway function (SAF) among the participants included. Age, smoking, male sex, worse SAF, and respiratory symptoms might cause the progressing from normal people to PRISm, then to COPD patients. Besides, the SAD indicators such as MMEFpred, FEF75pred, and FEF50pred were included in lung function tests and bronchodilator tests. Intriguingly, it was found that early diagnosing COPD via the SAD indicators might be feasible. In the future, early diagnosis for COPD requires further research.